The South American Biogeographic Transition Zone: An analysis from Asteraceae - Urtubey, Estrella (2010)
In order to elucidate the biotic diversification of Asteraceae inhabiting the South American Transition Zone, we undertook a panbiogeographic analysis (based on a parsimony analysis of endemicity) and a cladistic biogeographic analysis. The study units were the six biogeographic provinces of this zone plus the seven subregions of the Neotropical and Andean regions, considered as “outgroups”. Species analyzed belonged to the genera Arnaldoa, Barnadesia, Belloa, Berroa, Chevreulia, Chuquiraga, Cuatrecasiella, Dasyphyllum, Doniophyton, Duseniella, Facellis, Fulcaldea, Gamochaetopsis, Huarpea, Hypochaeris, Jalcophila, Lucilia, Luciliocline, and Schlechtendalia. A parsimony analysis of endemicity, based on presence/absence data of the 66 individual tracks ranged on two or more areas, allowed to identify four generalized tracks: (1) Coastal Peruvian Desert and Puna provinces; (2) Central Chilean, Patagonian, and Subantarctic subregions; (3) Amazonian, Chacoan, and Parana subregions; and (4) Puna province and Parana and Chacoan subregions. The Puna and Parana provinces, connected with two different generalized tracks each, constitute nodes. A cladistic biogeographic analysis, based on the paralogy–free subtrees extracted from the taxonomic area cladograms of Barnadesia, Chuquiraga, Dasyphyllum, Hypochaeris, and the Lucilia group, allowed obtaining a general area cladogram, which indicates a basic separation between the Atacama, Monte, and Prepuna provinces closely related to the Andean region, and the North Andean Paramo, Coastal Peruvian Desert, and Puna provinces closely related to the Neotropical region. Our results corroborate once again the transitional character of the provinces assigned to the South American Transition Zone, and allow speculating on their close affinities with the Andean and Neotropical regions.